Structure Evolution and Thermal Stability of High-Energy- Density Li-Ion Battery Cathode Li2VO2F. Issue 7 (1st January 2017) - Wang, Xiaoya; Huang, Yiqing; Ji, Dongsheng; Omenya, Fredrick; Karki, Khim; Sallis, Shawn; Piper, Louis F. J.; Wiaderek, Kamila M.; Chapman, Karena W.; Chernova, Natasha A.; Whittingham, M. Stanley
Abstract : Lithium-ion batteries (LIBs) provide high-energy-density electrochemical energy storage, which plays a central role in advancing technologies ranging from portable electronics to electric vehicles (EVs). However, a demand for lighter, more compact devices and for extended range EVs continues to fuel the need for higher energy density storage systems. Li2 VO2 F, which is synthesized in its lithiated state, allows two-electron transfer per formula during the electrochemical reaction providing a high theoretical capacity of 462 mAh/g. Herein, the synthesis and electrochemical performance of Li2 VO2 F are optimized. The thermal stability of Li2 VO2 F, which is related to the safety of a battery is studied by thermal gravimetric analysis. The structure and vanadium oxidation state evolution along Li cycling are studied by ex-situ X-ray diffraction and absorption techniques. It is shown that the rock-salt structure of pristine Li2 VO2 F is stable up to at least 250°C, and is preserved upon Li cycling, which proceeds by the solid-solution mechanism. However, not all Li can be removed from the structure upon charge to 4.5 V, limiting the experimentally obtained capacity.